Tobacco knowledge among adults in Zhejiang Province, China. - Yue Xu; Shuiyang Xu; Qingqing Wu; Yujie Guo (PLoS ONE, 2013)
The aims of current study were to assess the level of tobacco knowledge, anti-tobacco messages and major information channels in Zhejiang.Face-to-face interviews were conducted with 2112 adults in Zhejiang. Data on demographic information, smoking status, tobacco knowledge, anti-tobacco messages and major information channels was collected.The findings revealed that only 31.87% of the population were aware that smoking could cause all three diseases (stoke, heart disease, and lung cancer), 86.09% were aware that smoking causes lung cancer, 46.43% and 42.40% were aware that smoking causes stroke and heart attack, respectively. Residence and education level had significant effects on awareness, while the effects of smoking status, gender, age, and household monthly income were not significant. There were five major information channels as follows: television (67.52%), newspapers or magazines (40.79%), billboards (30.02%), public walls (24.72), and radio (23.79%). Respondents got the following anti-tobacco messages from mass media: "No smoking in public" (66.34%), "No smoking in front of other people" (35.18%) and "Not offering cigarettes to one another" (22.82%).The tobacco knowledge among residents in Zhejiang province is relatively poor. Improved information channels and content of anti-tobacco messages are necessary to increase the public's tobacco knowledge, particularly among rural residents and people with less education.